New Properties and Mitochondrial Targets of Polyphenol Agrimoniin as a Natural Anticancer and Preventive Agent - Tatiana A. Fedotcheva; Olga P. Sheichenko; Nadezhda I. Fedotcheva (MDPI AG, 2021)
Agrimoniin is a polyphenol from the group of tannins with antioxidant and anticancer activities. It is assumed that the anticancer action of agrimoniin is associated with the activation of mitochondria-dependent apoptosis, but its mitochondrial targets have not been estimated. We examined the direct influence of agrimoniin on different mitochondrial functions, including the induction of the mitochondrial permeability transition pore (MPTP) as the primary mechanism of mitochondria-dependent apoptosis. Agrimoniin was isolated from Agrimonia pilosa Ledeb by multistep purification. The content of agrimoniin in the resulting substance reached 80%, as determined by NMR spectroscopy. The cytotoxic effect of purified agrimoniin was confirmed on the cultures of K562 and HeLa cancer cells by the MTT assay. When tested on isolated rat liver mitochondria, agrimoniin at a low concentration (10 µM) induced the low-amplitude swelling, which was inhibited by the MPTP inhibitors ADP and cyclosporine A, activated the opening of MPTP by calcium ions and stimulated the respiration supported by succinate oxidation. Also, agrimoniin reduced the electron acceptor DCPIP in a concentration-dependent manner and chelated iron ions. Owing to all these properties, agrimoniin can stimulate apoptosis or activate mitochondrial functions, which can be helpful in the prevention and elimination of stagnant pathological states.